Documentary review on inclusive quality education in Ibero- American countries during the period 2016-2020. - Ulises Mestre Gómez; José Clemente Peralta Navarrete; Rosario del Pilar De-La-Mata- Huapaya; Flor María Ayala-Albites; Ricardo Carlos Zubiaga-Martel; Dayana Margarita Lescay Blanco (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper presents a quantitative study whose general objective was to conduct a bibliometric review of the literature on attention to diversity and inclusive education. Likewise, a critical analysis of its content was carried out from a qualitative approach in order to know the position of the different authors regarding the evolution and characteristics of inclusive education as a fundamental component of quality in educational institutions in Ibero-American countries. The data analysis was performed based on the information provided by the Scopus database, where search parameters were chosen to filter the research papers relevant to the topic under study, finding affinity with 168 documents published within the Ibero-American community during the period 2016- 2020, which were the object of the proposed analyses. The research papers were categorized according to their year of publication, country of origin participating authors, area of knowledge and type of publication, with the purpose of facilitating their interpretation.